Legal Analysis of Non-Performing Loans of Bank Sulut - Limboto Branch: Impact and Civil Perspective - Muhammad Tahta A.R; Weny Almoravid Dungga; Sri Nanang Meyske Kamba (Estudiante Law Journal, 2023)
settlement of bad debts made by debtors, is a violation of the program credit distribution program against sulut-go bank which has generated a lot of speculation about the rules of civil law. The problem is the enforcement of the law against the debtor allegedly with the issue of the article on the crime of corruption article 2 paragraph 1. The purpose of this research is to find out thoroughly about the enforcement of bad credit in the review of civil law. bad credit in the review of civil law and judge's decision, the problem of bad credit, and default. and default. Bank Sulut-Go which is in limboto branch against debtors who have bad credit. and discussion of the research that there is an imprudence that is done by the bank regarding the credit process by pledging something that does not belong to the debtor, but is processed.belonging to the debtor, but processed. Furthermore, that this contract occurs contract with a repayment duration that is not yet due but has already entered the court. The conclusion drawn by the researcher is that when a case that still has a contract it includes default and is a problem of bonding between people because it arises due to the cideranya promise, whose resolution path must be the civil realm. Default in bad credit can be recognized when there is an error.